T-regulatory cells in severe atopic dermatitis: alterations related to cytokines and other lymphocyte subpopulations - Samochocki, Zbigniew; Alifier, Marek; Bodera, Paweł; Jeziorkowska, Renata; Rosiak, Ewa; Jurkiewicz, Beata; Glińska, Olga; Gliński, Wiesław; Stankiewicz, Wanda (Archives of Dermatological Research, 2012)
The changes in lymphocyte subpopulations in atopic dermatitis (AD) concern also T-regulatory cells. We investigated the expression of various surface receptors on CD3 + CD4 + CD25 high FoxP3 + T-regulatory cells and the activation CD28 + receptor and the inhibitory CD152 + receptor on helper/inducer as well as cytotoxic/suppressor T cells. Peripheral blood lymphocytes of 15 AD patients and 20 healthy subjects were analyzed by flow cytometry using monoclonal antibodies. The concentrations of IL-6, IL-10 and TGF-β were determined in the serum and the supernatant of ConA-stimulated CD4 + lymphocytes. In AD patients the percentage of CD4 + CD25 high FoxP3 + as well as CD3 + CD8 + cells increased, which positively correlated with SCORAD index ( r = 0.55, p = 0.03). The concentrations of IL-10 in the CD4 + lymphocyte culture supernatants and the concentrations of TGF-β in the sera and the supernatant negatively correlated with the severity of AD ( p < 0.01, r = −0.63; p < 0.02, r = −0.64 and p < 0.03, r = −0.58, respectively), whereas the serum concentration of IL-6 correlated positively ( p < 0.003, r = 0.71). The regulatory cells expressed more CD62L and CD134 surface markers but less CD95. Reduced expression of the apoptotic CD95 receptor suggests that survival time of these cells is prolonged. Since CD62L and CD134 were upregulated, the enhanced modulatory effect of CD4 + CD25 high FoxP3 + cells seemed to be suggested, which may result in increased co-expression of CD28/CD152 on both CD4 + and CD8 + subpopulations.